Study of the importance of core cylinders in the monitoring of the compressive strength of the concrete. Issue 1 (March 2021) - De, J; Iglesia, La; Murillo, M; Borrero Restrepo, D
Abstract: The fulfillment of the resistance to the compression as a fundamental property of the concrete, during the process of execution of a work, constitutes great work for all the factors that intervene in the constructive process. The same concrete cannot be suitable for all structures, many times when using the same mixture, failures can occur with relevant damage. This situation frequently occurs at construction sites and resources must be allocated to repair structures to guarantee their useful life. This research aims to focus on the importance of performing compressive strength tests and taking enough samples for reliable results. For this purpose, 36 concrete test samples were taken from different structural elements of work according to the requirements of the standard. Subsequently, the laboratory tests were carried out at 7, 14, 28, and 56 days with a control cylinder, to analyze the behavior of each sample according to the concrete specifications requested for the different types of structures. From the results obtained, we could observe the differences in the percentages achieved by each of the samples and the type of failure presented, in turn, the importance of the control cylinder, for the monitoring of the strength of the concrete.